Intelligence decision systems in enterprise information management - Kahraman, Cengiz; Kaya, Ihsan; Cevikcan, Emre (EMERALD GROUP PUBLISHING LTD, 2011)
Purpose - The purpose of this paper is to show how intelligence techniques have been used in information management systems. Design/methodology/approach - The results of a literature review on intelligence decision systems used in enterprise information management are analyzed. The intelligence techniques used in enterprise information management are briefly summarized. Findings - Intelligence techniques are rapidly emerging as new tools in information management systems. Especially, intelligence techniques can be used to utilize the decision process of enterprises information management. These techniques can increase sensitiveness, flexibility and accuracy of information management systems. The hybrid systems that contain two or more intelligence techniques will be more used in the future. Originality/value - The intelligence decision systems are briefly introduced and then a literature review is given to show how intelligence techniques have been used in information management systems.
Keywords: Intelligence techniques; Decision support systems; Enterprise information management; Information management; EVOLUTIONARY COMPUTATION; MULTIAGENT SYSTEM; EVALUATION MODEL; NEURAL-NETWORKS; SAMPLE-SIZE; FUZZY; OPTIMIZATION; TECHNOLOGY; DESIGN; PERFORMANCE; Computer Science; Information Science & Library Science; Business & Economics